1996
DOI: 10.1073/pnas.93.10.4953
|View full text |Cite
|
Sign up to set email alerts
|

Role of the regulatory subunit of bovine pyruvate dehydrogenase phosphatase.

Abstract: Bovine pyruvate dehydrogenase phosphatase (PDP) is a Mg2+-dependent and Ca2+-stimulated heterodimer that is a member of the protein phosphatase 2C family and is localized to mitochondria. Insight into the function of the regulatory subunit of PDP (PDPr) has been gained. It Both phosphorylated El (P-E1) and PDP must be bound to the 60-mer icosahedral dihydrolipoamide acetyltransferase (E2) component of PDC to obtain a maximum rate of dephosphorylation. Ca>2 apparently mediates the specific binding of PDP to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 21 publications
(27 reference statements)
2
41
0
Order By: Relevance
“…These genes encode the E2 and E3 subunits of the PDH core enzyme (Dlat, Dld), the mitochondrial pyruvate transporter MPC1 (Brp44l), and the mitochondrial transporter of the PDH cofactor thiamine pyrophosphate (Slc25a19/DNC). A fifth gene, encoding the negative regulator of the PDH phosphatases (Pdpr) (27) was also identified as an E4F1 target gene by ChIP-seq in transformed fibroblasts, but not in ES cells (data not shown). does not bind.…”
Section: Resultsmentioning
confidence: 99%
“…These genes encode the E2 and E3 subunits of the PDH core enzyme (Dlat, Dld), the mitochondrial pyruvate transporter MPC1 (Brp44l), and the mitochondrial transporter of the PDH cofactor thiamine pyrophosphate (Slc25a19/DNC). A fifth gene, encoding the negative regulator of the PDH phosphatases (Pdpr) (27) was also identified as an E4F1 target gene by ChIP-seq in transformed fibroblasts, but not in ES cells (data not shown). does not bind.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic subunit (PDP1c) is in the phosphatase 2C class (28). The regulatory subunit (PDP1r) is a flavoprotein with a bound flavin adenine dinucleotide that influences the Mg 2ϩ concentration that is required for PDP1c activity (29,69). The second PDP isoform, PDP2, is found in liver and adipose tissue (18).…”
Section: Regulation Of Pdpmentioning
confidence: 99%
“…By comparing the properties of recombinant PDPc and the native PDH phosphatase heterodimer (PDPc bound to PDPr), we obtained insight into the function of PDPr. Jiangong Yan found that PDPr decreases the sensitivity of PDPc to Mg2+ and that spermine increases the sensitivity of PDH phosphatase but not PDPc to Mg2+, apparently by interacting with PDPr (Yan et al, 1996). We interpret these observations to indicate that PDPr blocks or distorts the Mg2+-binding site of PDPc and that spermine produces a conformational change in PDPr (allosteric effect) that reverses its inhibitory effect.…”
mentioning
confidence: 76%